COVID-19 Vaccine: Between Myth and Truth - Pier Paolo Piccaluga; Antonio Di Guardo; Anna Lagni; Virginia Lotti; Erica Diani; Mohsen Navari; Davide Gibellini (Vaccines, 2022)
Since December 2019, a pandemic caused by the newly identified SARS-CoV-2 spread across the entire globe, causing 364,191,494 confirmed cases of COVID-19 to date. SARS-CoV-2 is a betacoronavirus, a positive-sense, single-stranded RNA virus with four structural proteins: spike (S), envelope (E), membrane (M), and nucleocapsid (N). The S protein plays a crucial role both in cell binding and in the induction of a strong immune response during COVID-19 infection. The clinical impact of SARS-CoV-2 and its spread led to the urgent need for vaccine development to prevent viral transmission and to reduce the morbidity and mortality associated with the disease. Multiple platforms have been involved in the rapid development of vaccine candidates, with the S protein representing a major target because it can stimulate the immune system, yielding neutralizing antibodies (NAbs), blocking viral entry into host cells, and evoking T-cell immune responses. To date, 178 SARS-CoV-2 vaccine candidates have been challenged in clinical trials, of which 33 were approved by various national regulatory agencies. In this review, we discuss the FDA- and/or EMA-authorized vaccines that are mostly based on mRNA or viral vector platforms. Furthermore, we debunk false myths about the COVID-19 vaccine as well as discuss the impact of viral variants and the possible future developments.